Self-Efficacy: Meningkatkan Jiwa Kewirausahaan Di Era Digital - Marta, Rizkayeni; Ganefri; Yulastri, Asmar; Riyanda, Afif Rahman; Hasan, Hanapi; Yunus, Yuliawati (The Indonesian Journal of Computer Science, 2023)
In the digital era which is full of rapid changes and complex challenges, success in the world of entrepreneurship is not only determined by technical knowledge and skills, but also by psychological factors. The entrepreneurial spirit is very important economically and socially so that entrepreneurship is very important both economically and socially. One of the factors driving the entrepreneurial spirit in the digital era is self-efficacy. Self-efficacy is essential for the willingness to act entrepreneurially, to identify and seize opportunities. Self-efficacy plays an important role in building an entrepreneurial spirit. The method for writing this article adopts the literature review method, articles sourced from the Google Scholar, elsevier, tanfonline platforms. In an effort to improve the entrepreneurial spirit in the digital era, contributions from the world of education are needed, so that educational programs can influence individuals' self-efficacy and self-confidence, supporting them to try, learn, and persist in pursuing an entrepreneurial future. Thus, individuals who have high self-efficacy regarding entrepreneurship will have high self-confidence, thereby triggering enthusiasm to become someone who has an entrepreneurial spirit.